TAAT - Inauguration and Planning Meeting - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2018)
International Institute of Tropical Agriculture (IITA) and African Development Bank Group to launch a bold plan to revolutionize African agriculture. Scientists, development specialists, agricultural experts, representatives from national agricultural research and extension systems (NARES), and entrepreneurs from the private sector mainly from Africa will assemble in IITA, Ibadan, Nigeria on 22-25 January 2018, for the inauguration and planning workshop of the long-awaited African Development Bank (AFDB)-funded program called Technologies for African Agricultural Transformation (TAAT). The TAAT will execute an ambitious and bold plan to achieve rapid agricultural transformation across Africa by raising agricultural productivity along 9 Priority Intervention Areas and over 18 agricultural commodity value chains.